Drawing outdoors - Buitrago, Jairo (Greystone Kids, Greystone Books, 2022)
"Maybe your school has a playground, gym, computers, and a library. But at this school in a faraway mountain range, things are a little different. There's a blackboard, some chairs ... and not much else. But with the help of an extraordinary teacher and a little imagination, anything is possible! The students in this spirited picture book spend their days drawing dinosaurs outdoors. They draw astounding, spectacular creatures that come to life before their eyes, and turn their school into a wondrous place, where any child would want to go and learn."--